2018
DOI: 10.1097/tp.0000000000002041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Features of Plasma Cell-Rich Acute Rejection After Kidney Transplantation

Abstract: The results indicated that PCAR was an independent risk factor for allograft loss. PCAR presented with all types of rejection in the Banff 2015 criteria, and AMR/sAMR was associated with poor allograft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…We investigated the presence of plasma cells within allografts in our model. Although the exact effector function of intra-renal plasma cells and their role in allograft rejection is not fully understood, intra-renal plasma cells have been associated with chronic allograft rejection and poor prognosis [24,[33][34][35][36]. Although we have previously shown that anti-BAFF therapy reduced the number of splenic plasma cells [23], the difference in intra-renal plasma cells between groups was not statistically significant in this study.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…We investigated the presence of plasma cells within allografts in our model. Although the exact effector function of intra-renal plasma cells and their role in allograft rejection is not fully understood, intra-renal plasma cells have been associated with chronic allograft rejection and poor prognosis [24,[33][34][35][36]. Although we have previously shown that anti-BAFF therapy reduced the number of splenic plasma cells [23], the difference in intra-renal plasma cells between groups was not statistically significant in this study.…”
Section: Discussioncontrasting
confidence: 77%
“…Plasma cells are antibody-producing cells derived from B cells and have been found within kidney allograft infiltrates [24]. We therefore determined the amount of intra-renal plasma cells by staining for IgG + elliptical cells, as previously described [23].…”
Section: Effect Of Anti-baff Treatment On Intra-renal Plasma Cellsmentioning
confidence: 99%
“…Not only are suppression of NLR and PLR associated with ACR, but the underlying mechanism is from a relative increase in the lymphocyte count, which is expected given the pathogenesis of rejection. While flow cytometric detection of early T cell activation, CD69 expression has yielded mixed results [ 4 , 18 ], quantitative competitive RT-PCR assays measuring mRNA for cytotoxic effector molecule expression by PBMCs in renal transplant recipients have yielded more favorable results [ 4 , 17 , 19 , 20 ]. Compared to these techniques, a routinely obtained CBC with differential easily captures the inflammatory signature that precedes detection of allograft dysfunction and allows integration of this information with ongoing allograft and urinary immune biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (about 90%) of acute rejections, especially in the first year after ktx, are T cell-mediated [3]. However, emerging evidence has revealed that intra-graft B-cell accumulation plays an important role in T cell-mediated rejection as well and correlates with a worse outcome [4,5,6]. However, the mechanistic details are not completely resolved.…”
Section: Introductionmentioning
confidence: 99%